The Paris Agreement in Crisis: Legal and Environmental Consequences of the US Withdrawal - Wulandari, Putri Ayu; Aisyah, Nandhyra Syafa Nur; Buchori, Najwa Iqlima Azalia; Istiqomah, Nurul; Hardisafitri, Katlea (Universitas Negeri Semarang, 2024)
The United States' withdrawal from the Paris Agreement in 2017 created a significant impact on the international environmental legal order. As one of the largest carbon-emitting countries and a global leader, this decision sends a negative signal to other countries regarding the collective commitment to combat climate change. This article analyzes the domino effect that the move has had on countries' compliance with international environmental agreements. Using a normative approach and policy analysis, the research highlights how the US action affected the legitimacy and legal binding power of the Paris Agreement. The study finds that the US withdrawal weakened developing countries' incentives to comply with agreed emissions targets, given the absence of promised financial and technological support. Moreover, it exacerbates the trend of “free-riding,” where some countries are reluctant to contribute fully due to a lack of example from developed countries. On the other hand, the article also notes the positive response from non-state actors, such as local governments and multinational corporations, who are committed to furthering the goals of the Paris Agreement even without US federal support. The article concludes with recommendations to strengthen the international environmental legal framework to make it more adaptive to global political dynamics. In this way, the sustainability of such agreements depends not just on one country but on the collective commitment of the entire international community.